A Comparison of Bacteremic Pneumococcal Pneumonia with Nonbacteremic Community-Acquired Pneumonia of Any Etiology — Results from a Canadian Multicenter Study. Issue 7 (3rd October 2003) - Marrie, Thomas J; Low, Donald E; de Carolis, Emidio; the Canadian Community-Acquired Pneumonia Investigators
Abstract : BACKGROUND: Bacteremic pneumococcal pneumonia has not been the subject of a multicentre Canadian Study. OBJECTIVES: To compare bacteremic community-acquired Streptococcus pneumoniae pneumonia with nonbacteremic community-acquired pneumonia of any etiology. METHODS: A prospective cohort study was conducted at 15 centres in eight Canadian provinces from January 1996 to January 1998. RESULTS: Fifty-six of the 450 patients (12.4%) had one or more blood cultures positive for S pneumoniae . Compared with the 394 blood culture-negative patients, the bacteremic patients were younger (55.6 years versus 63.4 years; P=0.002). At presentation, bacteremic patients had a higher mean oral temperature (38.1±1.2°C versus 37.7±1.2°C; P=0.026), a higher pulse rate (108.4±22.1 beats/min versus 102.1±20.6 beats/min; P=0.033), a lower diastolic blood pressure reading (66.8±12.7 mmHg versus 73.8±15.8 mmHg; P=0.001) and a higher percentage of white blood cells that were band forms (22.1% versus 14.2%; P=0.0007). The time from onset of symptoms until admission to hospital was shorter among the bacteremic patients (4.6±3.7 days versus 7.0±13.9 days; P=0.005). Three capsular polysaccharide types accounted for 53.4% of the isolates: type 14, 29.2%; type 4, 12.1%; and type 22 F, 12.1%. Two of 44 isolates were resistant to penicillin. CONCLUSIONS: While some differences in patient characteristics and presentation occur when patients with bacteremic pneumococcal pneumonia are compared with nonbacteremic patients with community-acquired pneumonia, there is considerable overlap, and clinical presentation does not allow one to distinguish the bacteremic patients from the nonbacteremic patients.